An institutional perspective of the socioemotional-financial wealth relationship: Commentary on Martin and Gomez-Mejia's "The relationship between socioemotional and financial wealth: re-visiting family firm decision making". (21st November 2016) - Duran, Patricio
Abstract : Purpose: The purpose of this paper is to offer an institutional perspective of the Martin and Gomez-Mejia model. Specifically, this paper offers arguments of how institutions moderate the socioemotional wealth (SEW) and financial performance relationship. Design/methodology/approach: This is an individual commentary that explores country-level institutional contingencies that affect the predicted effect of SEW dimensions upon financial performance offered by Martin and Gomez-Mejia. Findings: The paper offers arguments of how both formal and informal institutions, such as the legal protection of minority shareholders, labor and investors; freedom of expression and information; and the country's culture, exacerbate or ameliorate the predicted effect of the five SEW dimensions upon financial performance. Originality/value: By exploring an institutional perspective of the socioemotional and financial wealth relationship, this commentary offers additional boundary conditions to those offered by Martin and Gomez-Mejia to further refine their theory.